2019
DOI: 10.1523/jneurosci.0806-19.2019
|View full text |Cite
|
Sign up to set email alerts
|

Differential Coding Strategies in Glutamatergic and GABAergic Neurons in the Medial Cerebellar Nucleus

Abstract: The cerebellum drives motor coordination and sequencing of actions at the millisecond timescale through adaptive control of cerebellar nuclear output. Cerebellar nuclei integrate high-frequency information from both the cerebellar cortex and the two main excitatory inputs of the cerebellum: the mossy fibers and the climbing fiber collaterals. However, how nuclear cells process rate and timing of inputs carried by these inputs is still debated. Here, we investigate the influence of the cerebellar cortical outpu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 86 publications
0
19
0
Order By: Relevance
“…The excitatory nuclei neurons have a higher firing frequency (Özcan et al . 2020) and a larger cell body (Uusisaari et al . 2007) compared to the inhibitory neurons.…”
Section: Resultsmentioning
confidence: 99%
“…The excitatory nuclei neurons have a higher firing frequency (Özcan et al . 2020) and a larger cell body (Uusisaari et al . 2007) compared to the inhibitory neurons.…”
Section: Resultsmentioning
confidence: 99%
“…Purkinje cells with the fastest firing capacity (Aldoc-negative: Xiao et al, 2014 ; Zhou et al, 2014 ) densely innervate the largest fastigial neurons (F1 R ), which in turn make extensive synapses onto somata and proximal dendrites of gigantic brainstem neurons responsible for rapid posturomotor reflexes ( Eccles et al, 1975a ). The largest glutamatergic fastigial cell types can transform Purkinje cell synaptic inhibition into precisely timed spikes ( Özcan et al, 2020 ), as has been shown for their counterparts in the interpositus and dentate nuclei ( Person and Raman, 2012 ). On the other hand, physiological properties of the smallest glutamatergic fastigial cell types (F3 and F4) have not been explicitly reported, likely reflecting challenges in isolating and targeting them for recordings.…”
Section: Discussionmentioning
confidence: 96%
“…These studies assume that premotor and nucleo-olivary neurons respond in roughly equivalent ways during behavior (Shadmehr, 2020). Differences in the intrinsic and synaptic properties of these neurons, however, raise the likelihood that this prediction may not be realized Najac & Raman, 2017;Özcan et al, 2020;Uusisaari & Knöpfel, 2008;Uusisaari et al, 2007;Uusisaari & Knöpfel, 2011). Moreover, our data suggest different cell types also differ in their input sources, further predicting diverse response properties.…”
Section: Cell Type Specific Input Tracing Using Monosynaptic Rabies Vmentioning
confidence: 69%